Analisis Perbedaan Kebijakan Luar Negeri Korea Selatan Dibawah Kepemimpinan Park Geun Hye dan Moon Jae In Terhadap Kepemilikan Senjata Nuklir Korea Utara - BAIQ ULFA SEPTI LESTARI; Lalu Puttrawandi Karjaya; Muhammad Sood (Indonesian Journal of Global Discourse, 2021)
This paper aims to analyze why there are differences in South Korea's foreign policy towards North Korean nuclear weapon ownership under the Park Geun Hye and Moon Jae In regimes. This difference can be seen from President Park's policies which tend to be conservative and repressive towards North Korea, while the policies pursued by President Moon tend to be more cooperative and humanist towards North Korea. The two leaders are known to be the best samples representing conservative and cooperative foreign policy towards North Korea. This research found that the differences in the leadership policies of President Park and President Moon were largely influenced by internal and external factors including background, curriculum vitae, values, perceptions, domestic and international situations, reaction actions between countries and interference from other countries. This study uses the theory of foreign decision making, namely internal and external settings, as well as the concept of foreign policy to answer the problem formulation because both are able to explain why these differences in policy can occur. This research also found the fact that policy differences between the two regimes had a major effect on the security stability of South Korea and the Korean Peninsula area where President Moon succeeded in minimizing conflict between the two Koreas by using a cooperative approach and was able to establish good relations with North Korea through his New Sunshine Policy.